The child care problem : an economic analysis - Blau, David (David M.) (Russell Sage Foundation, 2001)
Blau (economics, University of North Carolina-Chapel Hill) discusses problems of child care, such as low quality of care, lack of availability, high expense of care, and low earnings and high turnover of child care providers, from an economic perspective, focusing on conceptual issues, models, data, and empirical results. He describes the US child care market and presents economic models, analyzes aspects such as demand, supply, price, and determinants of quality, and looks at child care subsidy and regulation policies. He proposes a new child care policy that involves providing child care vouchers.